PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN DAN LEVERAGE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sofi Nurul Fatonah; Nani Rohaeni; Ade Samsinar (Universitas Bina Bangsa, 2022)
This study aims to determine the effect of firm size, firm age and leverage on earnings management in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period simultaneously and partially. The method used is a quantitative method that is intended for large data and in the form of numbers, including classical assumption test analysis and assumption test of data analysis with computer assistance through SPSS version 25 software. Based on the results of the t test (partial) the variables of firm size (X1) and earnings management (Y). The value of tcount > ttable (2,964 > 1,669) with a significance level of 0,004 (0,004 < 0,05). Company age (X2) and earnings management (Y) variables. The value of tcount < ttable (0.381 < 1.669). Leverage (X3) and earnings management (Y) variables. The value of tcount > ttable (2.509 > 1.669) with a significance level of 0.015 (0.015 < 0.05). Meanwhile, the results of the F test (simultaneous) of firm size (X1), firm age (X2) and leverage (X3) on earnings management (Y). The value of Fcount > Ftable (4.307 > 2.75) with a significance level of 0.008 (0.008 < 0.05). Based on the results of the study, firm size, firm age and leverage simultaneously have a significant effect on earnings management, partially firm size and leverage have a significant effect on earnings management, while firm age has no significant effect on earnings management